Implementation of Purchasing Raw Material Credit Using the MYOB Accounting V18 Application at PT Mitra Metal Sejati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
PT Mitra Metal Sejati is a company engaged in mechanical services and fabrication machining. In carrying out its business activities, the company requires the purchase of raw materials to be able to carry out its activities. Recording credit purchases is an important part of a company because later the recording is related to debts which are the obligations of a company. The purpose of this study is to provide fast and accurate computerized purchase and debt information. The research methodology that the author uses, there are several stages starting with planning, data collection, data processing, and data migration to the MYOB Accounting Plus V18 application. The recording of the purchase of raw materials at PT Mitra Metal Sejati still uses Microsoft Excel and has not been computerized so mistakes often occur. Errors or problems that occur at PT Mitra Metal Sejati such as: inputting accounts payable and making Purchase Orders (POs) as well as credit purchase reports both names of suppliers, incoming invoice numbers and nominal still use Microsoft Excel so that sometimes data input errors occur. As for these problems and with the development of the company, it needs a good information system to support its business activities, especially in purchasing credit which will be related to company debt. Implementing a credit and debt purchase report presentation at PT Mitra Metal Sejati using the MYOB Accounting Plus V18 accounting application. So that it can make it easier, faster, in recording credit purchases and presenting purchase and debt reports, and these reports can be used as decision making by management.